PRANATACARA LEARNING: MODELING, MIND MAPPING, E-LEARNING, OR HYBRID LEARNING? - Suwarna Dwijonagoro; Suparno Suparno (LPMPP Universitas Negeri Yogyakarta, 2019)
This research was aimed to examine the most effective learning model for Pranatacara (Master of Ceremony) course. By having effective learning, the students can master the skills at being a professional Pranatacara. The study used the experimental method with the pretest-posttest nonequivalent group design. Four parallel classes were given learning treatments each with modeling, mind mapping, e-learning, and hybrid learning. The data of the practice test were analyzed by the one-way Anova. The result indicates that there is a significant difference among the learning models. The hybrid learning can be considered as the most effective model to increase the total score, with the effectiveness of 11.58%; followed by modeling (5.58%); e-learning (4.10%); and mind mapping (3.54%) respectively. The hybrid learning was found as the most effective to improve the fluency score, i.e. 14.23%; followed by mind mapping (8.31%); modeling (4.74%) and e-learning (4.00%) respectively. Moreover, there was a significant difference in the effectiveness of vocal exercise. The highest increase in vocal score was through hybrid learning, with 10.85%; followed by modeling (10.09%); e-learning (4.39); and mind mappling (2.88%). Therefore, hybrid learning was declared as the most effective for learning Pranatacara courses and on the contraty, the e-learning was found as the most ineffective.